Pengaruh Intervensi Self-Management Terhadap Kepuasan Kerja Perawat di Rumah Sakit Tipe C Yogyakarta - Intening, Vivi Retno; Diah Listiani; I Wayan Sudarta; Yullya Permina (HEALTHY BEHAVIOR JOURNAL, 2024)
Background: Job satisfaction is a manifestation of the success of employees in carrying out their responsibilities at work. Self-management is self-regulation in the use of time, choices, interests, activities, and physical and mental balance. The results of measuring nurse job satisfaction amid the COVID-19 pandemic decreased and affected the quality of hospital services. Objective: This research aims to determine the effect of self-management interventions on nurse job satisfaction at type C private hospital in Yogyakarta. Methods: Pre-experimental research design, one group pre-posttest. The research population is nurses at type C private hospital in Yogyakarta. The sample in this study was 45 respondents using a total population technique as the sample. This study used the Minnesota Satisfaction Questionnaire and the intervention was carried out online meeting. Results: The majority was female with a percentage (86.7%), the ages of nurses were 31-38 years with the most (42.2%), Diploma III education dominated (82.3%). Wilcoxon obtained Asymp.Sig (2-tailed) worth 0.001. The value of 0.001 is less than 0.05, so H0 is rejected and H? is accepted. Conclusion: There is an effect of self-management interventions on the job satisfaction of nurses at type C private hospital in Yogyakarta.